Tilings, sub-tilings, and spectral sets on p-adic space - Kadir Mamateli (Open Mathematics)
In this article, we provide a characterization of tilings, sub-tilings, and spectral sets on the pp-adic space Qpd{{\mathbb{Q}}}_{p}^{d}. Our methods are based on pp-adic distributions and pp-adic Fourier analysis. We also obtained a sufficient condition and a necessary condition on tiling of functions by translation on Qpd{{\mathbb{Q}}}_{p}^{d}.